Chemical Composition and Calorific Power of tree species in the Peruvian Andes - Belito, E. E. (2021)
Many forest species of the Peruvian Andes are considered exceptional for having innumerable powers, such is the case of the calorific power product of the chemical composition of the species. This study was carried out in the Department of Huancavelica, Izcuchaca District, the analysis of samples was carried out at the National University of Central Peru and the National University of Agraria la Molina, where ASTM Standards were used to obtain data. The species that presented the highest calorific value was Caesalpinia spinosa with 4658.25 kcal / kg, since within its chemical composition it presented a greater amount of extractables and lignin, while the Vachellia macracantha and Tecoma stans species obtained 4422.05 and 4077.1 kcal / kg respectively. However, the three species studied prove to have an excellent calorific value due they are above 4000 kcal / kg.